HUBUNGAN KONSUMSI BUAH SAYUR DAN STATUS HAID DENGAN KEJADIAN DEPRESI PADA REMAJA DI INDONESIA (ANALISIS RISKESDAS 2018) - Michelle Beatrice (2021)
Depression is in the top third place for Years Lost due to Disability and most affects women worldwide. Depression rates in women are higher than in men and the first onset of depression often occurs in adolescence. This also reveals various factors such as behavioral factors, physical factors, and socio-demographic factors, so that the purpose of this study is to see the corelaton between fruit / vegetable consumption and status with depression in female adolescents in Indonesia based on Riskesdas 2018. Analysis using cross-sectional methods and research sample 40,809 adolescent girls. The analysis method used logistic regression to assess the condition of fruit/vegetable consumption and depression status depending on age, education, place of residence and to see the interactions. It was found that the prevalence of depression in adolescent girls was 8.1%. After controlled by the confounder variable, fruit/vegetable consumption had a protective effect (OR = 0.75, 95% CI: 0.747-0.768) and menstrual status is a risk factor (OR = 1.4, 95% CI: 1.371-1.429) for depression. In addition, it was found that education was the most dominant factor influencing depression (basic education compared to high: OR = 3.67, 95% CI: 3.37-3.99, secondary vs high education: OR = 3.2, 95% CI: 2.94-3.48). Three interactions were found, namely between the variables of menstruation and age, consumption of fruits/vegetables with the place of residence, and consumption of fruits/vegetables with education. It is hoped that interventions can continue to be carried out in adolescent girls through optimal UKS, UKJBM, and PKPR to increase youth awareness about mental health as a whole.